Fixed Time Robust Control Design for Partial Linearize Power System Model - Kumar V.; Mohanty S.R. (My University, 2025)
In the power system network with the synchronous generator (S.G) states are commonly under the threat of system uncertainties, which may destabilize the S.G states. Therefore, a robust stabilizing control scheme under system perturbations are the prerequisites for the power system networks. In this paper a fixed time robust control is proposed for the partial linearized power system network, which provides fixed time stabilization of state error variable using sliding mode-based state reliant exponent coefficient variable. First the power system single machine infinite bus dynamics are partially linearized using partial feedback linearization (PFL) procedure to second order dynamics for robust excitation control design. After that fixed time stabilization based robust control to single machine infinite bus system is applied. The stability of the proposed control scheme is analyzed based on rigorous Lyapunov criteria of stability. Simulation oriented study is presented to validate the efficacy of the proposed control technique. © 2021 IEEE.